Performance, carcass yield, and meat quality of broilers fed a diet containing Bacillus thuringiensis var. israelensis - Paola de Freitas Feltrin; Aline Piccini Roll; Camila Von Muhlen; Fabio Pereira Leivas Leite; Eduardo Gonçalves Xavier; Fernando Rutz; Victor Büttow Roll (Acta Scientiarum. Animal Sciences, 2025)
This study aimed to evaluate the effect of Bacillus thuringiensis var. israelensis (Bti) on the performance, organ weights, carcass yield, and meat quality of chickens. A total of 288 male and female one-day-old Cobb chicks were either fed or not fed with Bti at a dose of 1x108 CFU per gram of feed for a period of 42 days resulting in a 2x2 factorial scheme (Bti x sex) with four treatments and 12 replicates of six birds each. The treatments were: T1 - Males without Bti; T2 - Females without Bti; T3 - Males with Bti; and T4 - Females with Bti. Performance variables were assessed weekly. At the end of the trial, 48 chickens (12 birds per treatment) were euthanized to determine carcass yield, edible organ yield, and meat quality. The results indicate that none of the variables were significantly affected by Bti inclusion in the diet. Male chickens, regardless of the BTI factor, showed higher body weight gain and feed intake at 1-21, 22-41, and 1-42 days of age, as well as better feed conversion in the 1-21-day period, in addition to higher live weight, liver weight, and thigh and drumstick weight. In summary, the inclusion of Bacillus thuringiensis var. israelensis in the chickens' diet did not yield positive results, indicating that more studies are needed to optimize its use in poultry production. The performance differences observed between the sexes, with males outperforming females, are consistent with those reported in the poultry industry and scientific literature.